Calculation of mark coordinates in 400 m oval athletics tracks: - Matsubayashi, T.; Ohnuma, H. (Journal of High Performance Sport, 2025)
Performance analysis in racing disciplines, also known as race analysis, involves measuring split or lap times at specific positions or distances. Official times provide some data, but more detailed measurements must be taken for precise analysis. Filming with appropriately positioned cameras can detect athletes` passage at specific positions. Therefore, many studies have used that method for detailed event timing and race analysis. Nevertheless, the absence of marks indicating certain positions poses challenges. Geometric calculations can compensate for missing marks, but the calculations entail intensive effort. In this study, we examined methods for calculating mark coordinates of 400 m oval athletics tracks. Thereafter, the calculated results for two tracks with typical layouts were presented. Furthermore, two application examples for identifying additional analysis-point positions were demonstrated. No marks exist for some analysis-point positions, but this method allows calculation of appropriate positions and supports detailed race analysis.